Tobamovirus 3′-Terminal Gene Overlap May be a Mechanism for within-Host Fitness Improvement - Dorokhov, Yuri L.; Sheshukova, Ekaterina V.; Komarova, Tatiana V. (Frontiers in Microbiology, 2017)
Overlapping genes (OGs) are a universal phenomenon in all kingdoms, and viruses display a high content of OGs combined with a high rate of evolution. It is believed that the mechanism of gene overlap is based on overprinting of an existing gene. OGs help virus genes compress a maximum amount of information into short sequences, conferring viral proteins with novel features and thereby increasing their within-host fitness. Analysis of tobamovirus 3'-terminal genes reveals at least two modes of OG organization and mechanisms of interaction with the host. Originally isolated from Solanaceae species, viruses (referred to as Solanaceae infecting) such as Tobacco mosaic virus do not show 3'-terminal overlap between MP and CP genes but do contain ORF6, which overlaps with both genes. Conversely, tobamoviruses, originally isolated from Brassicaceae species (referred to as Brassicaceae infecting) and also able to infect Solanaceae plants, have no ORF6 but are characterized by overlapping MP and CP genes. Our analysis showed that the MP/CP overlap of Brassicaceae-infecting tobamoviruses results in the following: (i) ¬¬¬¬¬genome compression and strengthening of subgenomic promoters; (ii) CP gene early expression directly from genomic and dicistronic MP subgenomic mRNA using an internal ribosome entry site (IRES) and a stable hairpin structure in the overlapping region; (iii) loss of ORF6, which influences the symptomology of Solanaceae-infecting tobamoviruses; and (iv) acquisition of an IRES polypurine-rich region encoding an MP nuclear localization signal. We believe that MP/CP gene overlap may constitute a mechanism for host range expansion and virus adjustment to Brassicaceae plants.